Design of Solar-powered Automatic Shrimp Feeder based on the Internet of Things Technology - Boonraksa, Terapong; Boonraksa, Promphak (Directorate for Research and Community Services, Institut Teknologi Bandung, 2025)
This paper presents the design and implementation of a solar-powered automatic shrimp feeder utilizing IoT technology to enhance efficiency and precision in aquaculture. The core of the system is the DC motor operated feeder mechanism, and is capable of user defined customization like feeding scheduling, speed control, real time system monitoring etc. from distance through IoT integration via a smartphone. The motor speed can be adjusted to 1000, 1500, and 2000 rpm as per the requirement. Additionally, system can also monitor other water quality parameters like water temperature, pH and DO values, which are displayed via a smartphone. The experimental results confirm that the feeder perform as expected, it is capable of dispensing 5 kg of feed within 54 second, feeding up to 4.5 m depth when operating at 2000 rpm while consuming just 178.92 W power. The feeder is designed to autonomously determine its operating schedule, with users having the flexibility to adjust the timing at any point through the mobile application. This automation ensures consistent and efficient feeding aligned with aquaculture needs. Furthermore, the study includes a comprehensive cost analysis. The use of solar power and automation led to an annual cost reduction of 83.18% compared to manual labor. Over a ten-year period, the system achieved a total cost savings of 96.78%, amounting to 1,460,000 baht. Beyond enhancing feeding efficiency, the integration of IoT in shrimp farming substantially lowers labor expenses, contributing to a more sustainable and economically viable farming model.